Trends and disparities in tuberculosis burden in Kazakhstan and Mongolia (2017–2021): a comparative analysis using GBD metrics - Oyunzul Amartsengel; Malika Idayat; Alexander Rommel; Natalya Glushkova; Kairat Davletov; Malik Adenov; Naranzul Dambaa; Lkhagvasuren Khorolsuren; Elena von der Lippe (Frontiers in Public Health)
BackgroundIn Central Asia, respiratory diseases, particularly tuberculosis (TB), are widespread communicable diseases that significantly impact both individuals and health systems, posing a substantial burden. Research highlights the importance of assessing the impact of TB on global morbidity statistics, given its status as a prominent contributor to global morbidity rates and the cause of over a million deaths annually. Our study aims to assess the patterns and changes in the burden of TB in Mongolia and Kazakhstan.MethodsThe design is retrospective cross-sectional study. This study used the Global Burden of Disease (GBD) framework, which introduced disability-adjusted life years (DALY) as a measure of disease burden, combining mortality (Years of Life Lost, YLL) and morbidity (Years Lived with Disability, YLD). The calculations were based on standard GBD formulas, incorporating life expectancy data, age at death, and disease-specific disability weights. We calculated Mongolia’s and Kazakhstan’s national TB registration data from 2017 to 2021. From 2017 to 2021, Kazakhstan and Mongolia experienced significant declines in the burden of TB, as indicated by reductions in years of life lost and years living with disability.FindingsFrom 2017 to 2021, Kazakhstan’s YLL decreased by 18.2% and YLD by 36%, reflecting improved TB control. Mongolia experienced a 24.9% decline in YLL and a 39.4% reduction in YLD, although premature mortality in older men remains a challenge. These findings highlight the need for targeted interventions and healthcare equity to sustain TB control efforts. YLD rates remained low and had minimal impact on total DALYs, underlining the positive trends in reducing TB mortality and disability in both countries. Kazakhstan and Mongolia have significantly reduced the burden of TB, evidenced by reductions in DALY, YLL, and YLD rates.InterpretationThe results suggest that while TB control efforts have yielded positive results in both countries, Mongolia faces challenges in reducing TB-related mortality and morbidity, highlighting the need for targeted interventions and improved access to TB services. These results are consistent with global trends showing a declining TB burden due to improved diagnostics and treatment strategies but highlighting structural disparities that hinder uniform progress. Moreover, WHO estimates for the Western Pacific Region (WPR) and South-East Asia Region (SEAR) reported a slower increase in tuberculosis mortality trends from 2017 to 2021. Future research should focus on addressing the factors contributing to Mongolia’s persistently high TB burden, including access to healthcare, treatment adherence, and the role of comorbidities. In addition, expanding the scope of analysis to other Central Asian countries will provide a broader understanding of TB control efforts across the region.